Cathepsin S activity controls ischemia-induced neovascularization in mice. (15th March 2015) - Li, Xiang; Cheng, Xian Wu; Hu, Lina; Wu, Hongxian; Guo-Ping,; Hao, Chang-Ning; Jiang, Haiying; Zhu, Enbo; Huang, Zhe; Inoue, Aiko; Sasaki, Takeshi; Du, Qiuna; et al.
Abstract: Background: Evidence from human and animal studies has demonstrated elevated levels of the cysteine protease cathepsin S (CatS) in hypoxic atherosclerotic lesions. We hypothesized that silencing of CatS gene would suppress ischemia-induced angiogenic action. Methods and results: Left femoral artery ligation-induced ischemia in mice showed the increased expression and activity of CatS in the ischemic muscle. The CatS-deficiency (CatS −/− ) mice showed impaired functional recovery following hindlimb ischemia and reduced levels of peroxisome proliferator-activated receptor-γ (PPAR-γ), phospho-Akt (p-Akt), p-endothelial nitric oxide synthase, p-extracellular signal-regulated kinase1/2 (Erk1/2), p-p38 mitogen-activated protein kinase, and vascular endothelial growth factor (VEGF) proteins, as well as reduced levels of matrix metalloproteinase-9 and macrophage infiltration in the ischemic muscles. In vitro, CatS silencing reduced the levels of these targeted essential molecules for angiogenesis and vasculogenesis. Together, the results indicated that the effects of CatS knockdown led to defective endothelial cell invasion, proliferation, and tube formation. This notion was reinforced by the finding that CatS inhibition led to a decreased PPAR-γ level and VEGF/Erk1/2 signaling activation in response to ischemia. CatS −/− resulted in decreased circulating EPC-like CD31 + /c-Kit + cells, accompanied by the reduction of the cellular levels of PPAR-γ, p-Akt, and VEGF induced by ischemic stress. Transplantation of bone-marrow-derived mononuclear cells from CatS +/+ mice restored neovascularization in CatS −/− mice. Conclusions: CatS activity controls ischemia-induced neovascularization partially via the modulation of PPAR-γ and VEGF/Akt signaling activation. Highlights: Cathepsin S (CatS) protein and activity levels increased in injured mouse muscles in response to ischemia. Silencing CatS attenuated the vascular endothelial progenitor cell recruitment and homing into ischemic vasculature. Likewise, the CatS inhibitor Z-FL-COCHO diminished ischemia-induced angiogenic action.